Application of the Digital Company Concept in Retail Companies during the Covid-19 Pandemic - Nugraha, Ucu; Putra, Fadhil Satya (CENTRAL ASIA AND THE CAUCASUS, 2022)
During the pandemic, retail companies need to apply the concept of a digital company due to the many obstacles that prevent companies from running their business processes directly as usual. Therefore, companies need to design digital systems that can help business processes to be carried out digitally but still can get the same benefits even more than the old manual way by applying the concept of digital companies, digital marketing and ERP.